Resin composition, molded article, and laminate

The resin composition, comprising acrylic, propylene, and styrene thermoplastic elastomers, addresses the issue of insufficient adhesion strength at high temperatures by providing strong and durable adhesion to thermoplastic resins.

JP7662989B2Active Publication Date: 2025-04-16MCPP INNOVATION LLC
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021012172
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-01-28
Publication Date
2025-04-16
Estimated Expiration
2041-01-28

AI Technical Summary

Technical Problem

Existing resin compositions for laminating soft polyvinyl chloride resin with thermoplastic resins like polyolefin resin or polycarbonate resin exhibit insufficient adhesion strength, particularly at high temperatures.

Method used

A resin composition comprising an acrylic thermoplastic elastomer, a propylene elastomer, and a styrene thermoplastic elastomer, which provides good adhesion to thermoplastic resins and maintains heat-resistant adhesion even at high temperatures.

Benefits of technology

The resin composition achieves strong and durable adhesion to polyvinyl chloride and polyolefin resins, maintaining adhesive strength under high temperature conditions, thus addressing the limitations of prior art.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007662989000001
    Figure 0007662989000001
Patent Text Reader

Abstract

To provide a resin composition having excellent adhesion to a thermoplastic resin such as a polyvinyl chloride resin layer and a polyolefin resin layer and high adhesive strength even under a high temperature condition.SOLUTION: There are provided a resin composition containing a component (A), a component (B), and a component (C) below, a molded body obtained by molding the resin composition, a laminate having a layer containing the resin composition and another layer, and a construction material containing the laminate as a component. The component (A): acryl-based thermoplastic elastomer. The component (B): propylene-based elastomer. The component (C): styrene-based thermoplastic elastomer.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition having good adhesion to thermoplastic resins, a molded article of the resin composition, a laminate having a layer containing the resin composition, and a building material using the laminate. [Background technology]

[0002] As a base material for building materials such as wallpaper and decorative sheets, soft polyvinyl chloride resin substrates are often used because they are flexible and have good moldability. In addition, building materials made of soft polyvinyl chloride resin are also used that have been embossed or foamed in applications where improved touch and design are required. Soft polyvinyl chloride resins are also used in automobile interior parts because they have excellent flexibility and touch and are low cost. However, with the recent increasing demand for lighter automobiles for environmental protection and fuel efficiency, it is required to reduce the weight of soft polyvinyl chloride resin parts by laminating them with polyolefin resins or polycarbonate resins with lower specific gravity. Furthermore, when used as a member that is both lightweight and strong, it is also laminated with a metal plate such as aluminum.

[0003] Thus, various studies have been conducted to increase the adhesive strength between layers in laminates of a flexible polyvinyl chloride resin layer and a different material (a polyolefin resin layer, which is a thermoplastic resin layer other than flexible polyvinyl chloride resin, a saponified ethylene-vinyl acetate copolymer layer, or a metal plate).

[0004] For example, Patent Document 1 discloses a resin composition that contains an acrylic thermoplastic elastomer, a propylene-based elastomer having a specific density, and an ethylene-vinyl acetate copolymer as a resin composition that can improve the adhesive strength (heat-resistant adhesiveness) between a soft polyvinyl chloride resin layer and a polyolefin resin layer at high temperatures, and a laminate that uses this resin composition as a resin composition for an interlayer adhesive layer between a soft polyvinyl chloride resin layer and a polyolefin resin layer.

[0005] Furthermore, Patent Document 2 discloses a resin composition for bonding layers that has good adhesion to polyvinyl chloride resin layers, polycarbonate resin layers, and metal plates such as aluminum, and also has good adhesive strength against shear stress. The resin composition contains a polyester elastomer, a propylene-based elastomer having a specific density, and an ethylene-vinyl acetate copolymer, and discloses a laminate having an adhesive layer containing this resin composition and a polyvinyl chloride resin layer. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2018-16759 A [Patent Document 2] JP 2020-158667 A Summary of the Invention [Problem to be solved by the invention]

[0007] It was found that the adhesive strength at temperatures ranging from room temperature to high temperatures, particularly at high temperatures, is insufficient in a laminate using the resin composition described in Patent Document 1. That is, in Patent Document 1, the adhesive strength to a polyvinyl chloride resin layer or a polyolefin resin layer as an adhesive resin layer is evaluated by a 180° T peel test, but it was found that sufficient results were not obtained when evaluated by a shear peel test shown in the Examples section below. It was also found that the laminate using the resin composition described in Patent Document 2 exhibits high adhesive strength at room temperature but has insufficient adhesive strength at high temperatures. That is, in Patent Document 2, the adhesive strength of a polyvinyl chloride resin layer or a polyolefin resin layer as an adhesive resin layer to an aluminum plate is evaluated by a 90° peel test and a shear peel test at 23°C, but it was found that sufficient results were not obtained when evaluated by a shear peel test at a high temperature such as 80°C as shown in the Examples section below.

[0008] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a resin composition having excellent heat-resistant adhesiveness that has good adhesion to thermoplastic resins such as polyvinyl chloride resin and polyolefin resin and can sufficiently maintain adhesive strength even under high temperature conditions, and a molded body, a laminate, and a building material that use this resin composition. [Means for solving the problem]

[0009] Means for Solving the Problems The present inventors have conducted intensive research in view of the above problems and have found that the above problems can be solved by forming a resin composition containing an acrylic thermoplastic elastomer, a propylene-based elastomer, and a styrene-based thermoplastic elastomer, thereby completing the present invention. That is, the present invention relates to the following [1] to

[11] .

[0010] [1] A resin composition comprising the following components (A), (B) and (C): Component (A): Acrylic thermoplastic elastomer Component (B): Propylene-based elastomer Component (C): Styrene-based thermoplastic elastomer

[0011] [2] The resin composition according to [1], wherein the acrylic thermoplastic elastomer of component (A) is an acrylic block copolymer.

[0012] [3] The resin composition according to [2], wherein the acrylic thermoplastic elastomer of component (A) is a polymethyl methacrylate-polybutyl acrylate block copolymer.

[0013] [4] A molded article obtained by molding the resin composition according to any one of [1] to [3].

[0014] [5] A laminate having a layer containing the resin composition according to any one of [1] to [3] and another layer.

[0015] [6] The laminate according to [5], which has at least a first layer and a second layer as the other layers, and has a layer containing the resin composition between the first layer and the second layer.

[0016] [7] The laminate according to [5] or [6], wherein the other layer is a resin layer containing a thermoplastic resin.

[0017] [8] The laminate according to [7], wherein the resin layer containing the thermoplastic resin includes a polyvinyl chloride resin layer.

[0018] [9] The laminate according to [6], wherein the first layer is a polyvinyl chloride resin layer or a polyolefin resin layer, and the second layer is a polyvinyl chloride resin layer or a polyolefin resin layer.

[0019]

[10] The laminate according to [9], wherein the first layer is a polyvinyl chloride resin layer and the second layer is a polyolefin resin layer.

[0020]

[11] A building material comprising the laminate according to any one of [5] to

[10] as a component. Effect of the Invention

[0021] According to the present invention, there are provided a resin composition that has good adhesion to thermoplastic resins such as polyvinyl chloride resin and polyolefin resin and can sufficiently maintain adhesive strength even under high temperature conditions, and a molded body, a laminate, and a building material that use this resin composition. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] The present invention will be described in detail below, but the present invention is not limited to the following description, and can be modified as desired without departing from the gist of the present invention. In the present invention, when a numerical value or physical property value is enclosed before and after "~", the value before and after the "~" is included.

[0023] [Resin composition] The resin composition of the present invention contains the following components (A), (B) and (C). Component (A): Acrylic thermoplastic elastomer Component (B): Propylene-based elastomer Component (C): Styrene-based thermoplastic elastomer

[0024] <Component (A)> The component (A) used in the resin composition of the present invention is an acrylic thermoplastic elastomer, which is effective in improving adhesion and heat-resistant adhesion to polar resins, such as polyvinyl chloride resins, among other thermoplastic resins.

[0025] The acrylic thermoplastic elastomer of component (A) is usually a block copolymer having a hard segment with a glass transition temperature of room temperature (23° C.) or higher and a soft segment with flexibility.

[0026] In component (A), the glass transition temperature based on the hard segment is preferably 25°C or higher, more preferably 30°C or higher, and even more preferably 40°C or higher, while it is preferably 200°C or lower, more preferably 180°C or lower, and even more preferably 150°C or lower. The above-mentioned range of glass transition temperature is preferable from the viewpoint of heat resistance, moldability, etc. In the present invention, the glass transition temperature of component (A) means the peak temperature of loss tangent (tan δ) observed when a test piece is heated by a dynamic viscoelasticity measuring device under the conditions of a temperature range of -100 to 280°C, a heating rate of 5°C / min, and a frequency of 10 Hz. In a thermoplastic elastomer having multiple blocks, multiple loss tangent peaks are usually observed, but in this case, the peak on the low temperature side is derived from the soft segment, and the peak on the high temperature side is derived from the hard segment.

[0027] In terms of flexibility based on the soft segment, the lower limit of the hardness of component (A) is preferably 10 or more, more preferably 20 or more, in Duro A hardness, while the upper limit of the hardness is preferably 80 or less, more preferably 70 or less, in Duro A hardness. The hardness in the above range is preferable from the viewpoint of heat-resistant adhesion to polyvinyl chloride resin. The Duro A hardness of component (A) is a value measured in accordance with ISO 7619.

[0028] The hard segment of component (A) is preferably a polymer block obtained from one or more of the following (meth)acrylic monomers. Examples of such (meth)acrylic monomers include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, phenyl (meth)acrylate, hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, glycidyl (meth)acrylate, methoxyethyl (meth)acrylate, ethoxyethyl (meth)acrylate, butoxyethyl (meth)acrylate, and phenoxyethyl (meth)acrylate. Among these, methyl methacrylate, ethyl methacrylate, and butyl methacrylate are preferred, and methyl methacrylate is particularly preferred. That is, it is particularly preferred that the hard segment of component (A) is a polymer block of methyl methacrylate.

[0029] The soft segment of component (A) is preferably a polymer block obtained from one or more of the following (meth)acrylic monomers. Examples of such (meth)acrylic monomers include n-propyl (meth)acrylate, n-butyl (meth)acrylate, sec-butyl (meth)acrylate, n-hexyl (meth)acrylate, ethylhexyl (meth)acrylate, n-heptyl (meth)acrylate, n-octyl (meth)acrylate, and phenylethyl (meth)acrylate. Among these, n-propyl acrylate, n-butyl acrylate, sec-butyl acrylate, n-hexyl acrylate, ethylhexyl acrylate, n-heptyl acrylate, n-octyl acrylate, and phenylethyl acrylate are preferred, and n-butyl acrylate is particularly preferred. That is, the soft segment of component (A) is particularly preferably a polymer block of n-butyl acrylate.

[0030] The acrylic thermoplastic elastomer of component (A) preferably has a weight ratio of hard segment to soft segment ([weight of hard segment] / [weight of soft segment]) of 10 / 90 to 70 / 30, more preferably 15 / 85 to 60 / 40.

[0031] The weight average molecular weight (Mw) of component (A) is preferably 20,000 or more, more preferably 30,000 or more, and even more preferably 40,000 or more, while it is preferably 600,000 or less, more preferably 400,000 or less, and even more preferably 200,000 or less. The ratio of the weight average molecular weight (Mw) to the number average molecular weight (Mn) of component (A), i.e., the molecular weight distribution (Mw / Mn), is usually 1.1 to 5.0, and preferably 1.1 to 3.0.

[0032] Here, the weight average molecular weight (Mw) and number average molecular weight (Mn) can be measured by gel permeation chromatography (GPC) under the following conditions. Equipment: Tosoh HLC-8120 Column: Inertsil WF300 Solvent: Tetrahydrofuran Calibration: Polystyrene

[0033] The specific gravity of component (A) is preferably 0.90 or more, more preferably 1.00 or more, and even more preferably 1.10 or more, while it is preferably 1.40 or less, more preferably 1.30 or less, and even more preferably 1.20 or less. Here, the specific gravity can be measured by (ISO1183-A method (measurement temperature: 23°C)).

[0034] The acrylic thermoplastic elastomer of component (A) is commercially available, and can be selected from, for example, the Clarity (registered trademark) series manufactured by Kuraray Co., Ltd., the Nabstar (registered trademark) series manufactured by Kaneka Corporation, and the like.

[0035] In the resin composition of the present invention, the acrylic thermoplastic elastomer of component (A) may be used alone or in combination of two or more types having different hard segment and soft segment compositions, physical properties, etc.

[0036] <Ingredient (B)> The resin composition of the present invention contains a propylene-based elastomer as component (B). The propylene-based elastomer is blended to provide adhesion to polyolefin resins and heat-resistant adhesion. The propylene-based elastomer of component (B) may be any elastomer containing monomer units derived from propylene as the main component, and preferably has a propylene content (the mass ratio of monomer units derived from propylene to all monomer units) of 50 mass% or more.

[0037] The propylene content of the propylene-based elastomer of component (B) is more preferably 55% by mass or more, and even more preferably 60% by mass or more. On the other hand, the upper limit of the propylene content of component (B) is not particularly limited, but is usually 90% by mass or less, preferably 88% by mass or less, and more preferably 86% by mass or less. In component (B), the propylene content is preferably the above lower limit or more from the viewpoint of adhesion to polypropylene-based resins, and is preferably the above upper limit or less from the viewpoint of compatibility with the styrene-based thermoplastic elastomer of component (C).

[0038] The propylene-based elastomer of component (B) preferably contains other copolymerization components in addition to propylene from the viewpoint of compatibility with the styrene-based thermoplastic elastomer. Examples of such other copolymerization components include ethylene, 1-butene, 2-methylpropylene, 1-pentene, 3-methyl-1-butene, 1-hexene, 4-methyl-1-pentene, and 1-octene, and among these, ethylene, 1-butene, 1-pentene, 1-hexene, and 1-octene are preferred, and ethylene and 1-butene are more preferred. The above-mentioned other copolymerization components may contain only one type or two or more types.

[0039] The density of component (B) (ASTM D1505) is 0.855 to 0.895 g / cm 3 If the density of component (B) is within the above range, it is easy to impart the effect of maintaining good adhesiveness to a resin composition containing component (B). The density (ASTM D1505) of component (B) is more preferably 0.860 to 0.880 g / cm 3 It is.

[0040] From the viewpoint of moldability, it is preferable that component (B) has a melt flow rate (MFR) of 1 to 60 g / 10 min, measured according to JIS K7210 (1990) at 230° C. under a load of 21.2 N. From this viewpoint, the MFR of component (B) is more preferably 2 to 50 g / 10 min.

[0041] The propylene-based elastomer of component (B) can be produced by a known polymerization method using a known olefin polymerization catalyst. For example, a polymerization method using a Ziegler-Natta catalyst can be used. For this polymerization method, a slurry polymerization method, a solution polymerization method, a bulk polymerization method, a gas phase polymerization method, etc. can be used, and two or more of these methods can be combined to produce the elastomer.

[0042] The propylene-based elastomer of component (B) is commercially available and can be appropriately selected from commercially available products such as the "Tafmer (registered trademark)" series manufactured by Mitsui Chemicals, Inc., the "Vistamaxx (registered trademark)" manufactured by ExxonMobil Corporation, and the "Zelas" series manufactured by Mitsubishi Chemical Corporation.

[0043] In the resin composition of the present invention, the propylene-based elastomer of component (B) may be used alone or in combination of two or more types having different copolymerization component compositions, physical properties, and the like.

[0044] <Ingredient (C)> The component (C) used in the resin composition of the present invention is a styrene-based thermoplastic elastomer. The styrene-based thermoplastic elastomer of the component (C) acts to blend the above-mentioned components (A) and (B) and enhances the adhesiveness and heat-resistant adhesiveness of the resin composition of the present invention to thermoplastic resins.

[0045] The styrene-based thermoplastic elastomer of component (C) is preferably a block copolymer selected from the group consisting of block copolymers having at least one polymer block P derived from a vinyl aromatic compound and at least one polymer block Q derived from a conjugated diene, and block copolymers obtained by hydrogenating such block copolymers (hydrogenated block copolymers).

[0046] It is more preferred that polymer block P of component (C) is a polymer block of a monomer mainly composed of a vinyl aromatic compound, while polymer block Q is a polymer block of a monomer mainly composed of a conjugated diene, where "mainly composed" means that the content in the block is 50 mol % or more.

[0047] The vinyl aromatic compound as a monomer constituting the polymer block P is not limited, but is preferably a styrene derivative such as styrene, α-methylstyrene, or chloromethylstyrene. Of these, it is preferable to use styrene as the main component. These may be used alone or in combination of two or more. The polymer block P may contain a monomer other than the vinyl aromatic compound as a raw material.

[0048] The monomer constituting the polymer block Q is not limited, but preferably includes butadiene alone, isoprene alone, a mixture of butadiene and isoprene, etc. These may be used alone or in combination of two or more. Note that the polymer block Q may contain monomers other than butadiene and isoprene as raw materials.

[0049] Furthermore, the polymer block Q may be a hydrogenated derivative in which the double bonds contained therein are hydrogenated after polymerization, i.e., a hydrogenated block copolymer. The hydrogenation rate of the polymer block Q is not limited, but is preferably 50 to 100% by mass, and more preferably 80 to 100% by mass. By hydrogenating the polymer block Q within the above range, the thermal stability tends to be improved. The same applies to the case in which the polymer block P is made using a diene component as a raw material. The hydrogenation rate is, 13 It can be measured by C-NMR.

[0050] The styrene content of the styrene thermoplastic elastomer of component (C) is preferably 8 to 70% by mass. When the styrene content of the styrene thermoplastic elastomer is equal to or higher than the above lower limit, the compatibility with component (A) tends to be good, and when it is equal to or lower than the above upper limit, the moldability tends to be good. The styrene content of the styrene thermoplastic elastomer is more preferably 10 to 50% by mass. The "styrene content" in component (C) is used to mean not only the content of styrene units, but also the content of structural units in which an atom or atomic group other than a hydrogen atom is substituted on the aromatic ring of a styrene unit. The styrene content is 13 It can be measured by C-NMR.

[0051] The chemical structure of the copolymer having the polymer block P and the polymer block Q in the styrene-based thermoplastic elastomer of component (C) may be any of linear, branched, radial, etc., but is preferably a block copolymer represented by the following formula (1) or (2).

[0052] Furthermore, the block copolymer represented by the following formula (1) or (2) is preferably a hydrogenated derivative (hydrogenated block copolymer). When the copolymer represented by the following formula (1) or (2) is a hydrogenated block copolymer, the adhesiveness of the resin composition of the present invention tends to be good. P-(QP) m (1) (PQ) n (2) (In the formula, P represents a polymer block P, Q represents a polymer block Q, m represents an integer of 1 to 5, and n represents an integer of 1 to 5.)

[0053] In formula (1) or (2), the larger the m and n, the better in terms of lowering the order-disorder transition temperature of the rubber-like polymer, but the smaller the m and n, the better in terms of ease of production and cost.

[0054] As the block copolymer and / or hydrogenated block copolymer of a styrene-based thermoplastic elastomer (hereinafter collectively referred to as "(hydrogenated) block copolymer"), the (hydrogenated) block copolymer represented by formula (1) is more preferable than the (hydrogenated) block copolymer represented by formula (2) because of its excellent rubber elasticity.

[0055] The styrene-based thermoplastic elastomer of component (C) may have a polar group, if necessary. Examples of the polar group include a hydroxyl group, a carboxyl group, a carbonyl group, a thiocarbonyl group, an acid halide group, an acid anhydride group, a thiocarboxylic acid group, an aldehyde group, a thioaldehyde group, a carboxylate group, an amide group, a sulfonic acid group, a sulfonate group, a phosphoric acid group, a phosphoric acid ester group, an amino group, an imino group, a nitrile group, a pyridyl group, a quinoline group, an epoxy group, a thioepoxy group, a sulfide group, an isocyanate group, and an isothiocyanate group.

[0056] Examples of the styrene-based thermoplastic elastomer of component (C) include styrene-butadiene block copolymers and / or their hydrogenated products, styrene-isoprene block copolymers and / or their hydrogenated products, and styrene-butadiene-isoprene block copolymers and / or their hydrogenated products. Examples of hydrogenated styrene-butadiene block copolymers include styrene-butadiene-butylene-styrene copolymers (SBBS), styrene-ethylene-butylene-styrene copolymers (SEBS), and amine-modified styrene-ethylene-butylene-styrene copolymers (SEBS). Examples of hydrogenated styrene-isoprene block copolymers include styrene-ethylene-propylene-styrene copolymers (SEPS).

[0057] The upper limit of the number average molecular weight of the styrene-based thermoplastic elastomer of component (C) is not limited, but is usually 250,000 or less, preferably 230,000 or less, more preferably 210,000 or less, and even more preferably 200,000 or less. The lower limit of the number average molecular weight of the styrene-based thermoplastic elastomer is not limited, but is usually 20,000 or more, preferably 40,000 or more, and more preferably 50,000 or more. When the number average molecular weight of the styrene-based thermoplastic elastomer is within the above range, the moldability tends to be good. The number average molecular weight of the styrene-based thermoplastic elastomer of component (C) is a value measured in terms of polystyrene by gel permeation chromatography (hereinafter sometimes abbreviated as GPC).

[0058] The melt flow rate (MFR) of component (C), measured in accordance with JIS K7210 (1990) at 230°C under a load of 21.2 N, is not limited, but is preferably 0.01 to 100 g / 10 min, more preferably 0.03 to 90 g / 10 min, and even more preferably 0.05 to 80 g / 10 min. When the MFR of component (C) is within the above range, moldability tends to be good.

[0059] The density (ASTM D1505) of the component (C) is preferably 0.860 to 1.000 g / cm from the viewpoint of blocking properties. 3 and more preferably 0.870 to 1.000 g / cm 3 and more preferably 0.880 to 1.000 g / cm 3 It is.

[0060] Furthermore, the hardness of component (C) is not particularly limited, but is preferably 20 or more, more preferably 25 or more, even more preferably 30 or more, and particularly preferably 35 or more, in Shore A hardness (JIS K6253), and is preferably 95 or less, more preferably 93 or less, and even more preferably 90 or less. When the hardness of component (C) is within the above range, flexibility tends to be good.

[0061] The method for producing the styrene-based thermoplastic elastomer of component (C) is not particularly limited, and may be any method as long as the above-mentioned structure and physical properties can be obtained. The styrene-based thermoplastic elastomer of component (C) can be obtained, for example, by block polymerization in an inert solvent using a lithium catalyst or the like. In addition, the hydrogenation (hydrogenation) of the block copolymer can be performed in an inert solvent in the presence of a hydrogenation catalyst or other known methods.

[0062] The styrene-based thermoplastic elastomer used as component (C) of the present invention may be a commercially available product. Examples of commercially available products include the "KRATON" series manufactured by Kraton Polymers, and the "Tuftec (registered trademark)" and "SOE (registered trademark)" series manufactured by Asahi Kasei Corporation. An appropriate product may be selected from these commercially available products and used.

[0063] In the resin composition of the present invention, the styrene-based thermoplastic elastomer as component (C) may be used alone or in combination of two or more types having different copolymer component compositions, physical properties, and the like.

[0064] <Other ingredients> The resin composition of the present invention may contain resin components other than components (A), (B), and (C) (hereinafter, sometimes referred to as "other resins"), various additives, fillers, and the like, within the scope of not significantly impairing the effects of the present invention.

[0065] Examples of other resins include thermoplastic resins and various thermoplastic elastomers such as polyolefin resins (excluding those contained in component (B)); polyphenylene ether resins; polyamide resins such as nylon 6, nylon 66, and nylon 11; polyester resins such as polyethylene terephthalate and polybutylene terephthalate; (meth)acrylic resins such as polymethyl methacrylate resins (excluding those contained in component (A)); and styrene resins such as polystyrene (excluding those contained in component (C)). These other resins may be used alone or in any combination and ratio of two or more kinds.

[0066] Examples of additives include various heat stabilizers, antioxidants, ultraviolet absorbers, light stabilizers, antiaging agents, nucleating agents, plasticizers, impact modifiers, compatibilizers, defoamers, thickeners, crosslinking agents, surfactants, lubricants, release agents, antiblocking agents, processing aids, antistatic agents, flame retardants, flame retardant assistants, colorants, fillers, etc. These additives may be used alone or in any combination and ratio of two or more kinds.

[0067] Examples of the heat stabilizer and antioxidant include hindered phenols, phosphorus compounds, hindered amines, sulfur compounds, copper compounds, and alkali metal halides.

[0068] The resin composition of the present invention is preferably blended with an antiblocking agent as an additive. By blending the antiblocking agent, the blocking resistance between pellets of the resin composition of the present invention during the pellet production process and during subsequent storage, transportation, etc., tends to be improved. Examples of the antiblocking agent include polyolefin fine powder, polyethylene wax, and dispersions thereof.

[0069] Flame retardants are broadly classified into halogen-based and non-halogen-based flame retardants, with non-halogen-based flame retardants being preferred from an environmental perspective. Examples of non-halogen-based flame retardants include phosphorus-based flame retardants, hydrated metal compound (aluminum hydroxide, magnesium hydroxide) flame retardants, nitrogen-containing compound (melamine-based, guanidine-based) flame retardants, and inorganic compound (borate, molybdenum compound) flame retardants.

[0070] Fillers are broadly classified into organic fillers and inorganic fillers. Examples of organic fillers include starch, cellulose fine particles, wood flour, soybean pulp, rice husks, bran, and other naturally derived polymers and modified products thereof. Examples of inorganic fillers include talc, calcium carbonate, zinc carbonate, wollastonite, silica, alumina, magnesium oxide, calcium silicate, sodium aluminate, calcium aluminate, sodium aluminosilicate, magnesium silicate, glass balloons, carbon black, zinc oxide, antimony trioxide, zeolite, hydrotalcite, metal fibers, metal whiskers, ceramic whiskers, potassium titanate, boron nitride, graphite, and carbon fibers. These fillers may be used alone or in any combination and ratio of two or more.

[0071] <Blend amount> In the resin composition of the present invention, the content of component (A) relative to the total amount of components (A), (B) and (C) is preferably 20 to 65% by mass. In terms of adhesion to polyvinyl chloride resin, it is preferable that the content of component (A) relative to the total amount of components (A), (B) and (C) is 20% by mass or more, while in terms of adhesion to polypropylene resin, it is preferable that the content of component (A) is 65% by mass or less. From these viewpoints, the content of component (A) is more preferably 23% by mass or more, and even more preferably 25% by mass or more, while more preferably 60% by mass or less, and even more preferably 55% by mass or less.

[0072] In the resin composition of the present invention, the content of component (B) relative to the total amount of components (A), (B) and (C) is preferably 20 to 65% by mass. A content of component (B) of 20% by mass or more is preferred from the viewpoint of compatibility and adhesiveness with polyolefin resins, while a content of component (B) of 65% by mass or less is preferred from the viewpoint of adhesiveness with polyvinyl chloride resins. From these viewpoints, the content of component (B) is more preferably 25% by mass or more, even more preferably 27% by mass or more, while more preferably 50% by mass or less, even more preferably 45% by mass or less.

[0073] In the resin composition of the present invention, the content of component (C) relative to the total amount of components (A), (B) and (C) is preferably 10 to 50 mass%. Component (C) is a component that disperses components (A) and (B). A content of component (C) of 10 mass% or more is preferable from the viewpoint of compatibility between components (A) and (B), while a content of component (C) of 50 mass% or less is preferable from the viewpoint of adhesion to polyolefin resin. From these viewpoints, the content of component (C) is more preferably 13 mass% or more, even more preferably 15 mass% or more, while more preferably 47 mass% or less, even more preferably 45 mass% or less.

[0074] When the resin composition of the present invention contains the above-mentioned other resins, the content is not limited, but is usually 0.1 to 20 mass%, preferably 0.5 to 10 mass%, based on 100 mass% of the resin composition. If the content of the other resins is equal to or less than the upper limit, the obtained resin composition can have sufficient adhesion to thermoplastic resins.

[0075] The content of the additives in the resin composition of the present invention is not limited, but is usually 0.01 to 10 mass%, preferably 0.2 to 5 mass%, based on 100 mass% of the resin composition. If the content of the additives is equal to or less than the upper limit, the resulting resin composition can have sufficient adhesion to polyvinyl chloride resin. When the resin composition of the present invention is used as a master batch, these additives can be contained at a concentration of 2 to 50 times, preferably 3 to 30 times, the above-mentioned content.

[0076] <Duro D hardness> The Duro D hardness of the resin composition of the present invention is not limited, but the lower limit of the value measured according to JIS K6253 is preferably 25 or more, more preferably 35 or more, while the upper limit of the hardness is preferably 80 or less, more preferably 70 or less. A hardness in the above range is preferable from the viewpoint of heat-resistant adhesion to polyvinyl chloride resin.

[0077] The flexural modulus of the resin composition of the present invention is not limited, but the lower limit of the value measured according to JIS K7171 is preferably 100 MPa or more, more preferably 130 MPa or more, while the upper limit of the hardness is preferably 1000 MPa or less, more preferably 800 MPa or less. The hardness in the above range is preferable from the viewpoint of heat-resistant adhesion to polyvinyl chloride resin and moldability.

[0078] <Melt flow rate (MFR)> The melt flow rate (MFR) of the resin composition of the present invention is not limited, but is preferably in the range of usually 0.2 to 60 g / 10 min, preferably 1 to 30 g / 10 min, more preferably 2 to 25 g / 10 min, as measured at 190° C. and a load of 21.2 N according to JIS K7210 (1999). If the MFR is equal to or less than the upper limit, the extrusion moldability of the resin composition tends to be good, and further, the mechanical strength of the laminate tends to be improved. If the MFR is equal to or more than the lower limit, the flowability is good, and therefore the moldability of the resin composition tends to be improved.

[0079] <Method of producing resin composition> The resin composition of the present invention can be obtained by mixing the above-mentioned components in a predetermined ratio. There is no particular restriction on the mixing method as long as the raw material components are uniformly dispersed. That is, by mixing the above-mentioned raw material components simultaneously or in any order, a resin composition in which each component is uniformly dispersed can be obtained. For more uniform mixing and dispersion, it is preferable to melt-mix a predetermined amount of the above-mentioned raw material components. For example, the raw material components of the resin composition of the present invention may be mixed in any order and then heated, or all the raw material components may be mixed while being melted sequentially, or the raw material components may be appropriately blended (dry blended) and melt-mixed during molding to produce the desired molded product.

[0080] The mixing method and mixing conditions are not particularly limited as long as each raw material component is mixed uniformly, but from the viewpoint of productivity, for example, a method of mixing the raw materials using a tumbler blender, V blender, ribbon blender, Henschel mixer, etc., and melt-kneading with a continuous kneader such as a single-screw extruder or a twin-screw extruder, and a batch-type kneader such as a mill roll, a Banbury mixer, or a pressure kneader is preferable. The manufacturing conditions when producing a resin composition by these methods are not limited, and can be appropriately set under well-known conditions. The temperature during melt mixing may be a temperature at which at least one of the raw material components is in a molten state, but usually a temperature at which all the raw material components used are melted is selected, and it can be generally performed at 150 to 250 ° C.

[0081] [Molded body] The molded article obtained from the resin composition of the present invention is not limited, and can be various extrusion molded articles or injection molded articles. The manufacturing method of the molded article is also not particularly limited, and specifically includes various molding methods such as injection molding, blow molding, extrusion molding, and inflation molding, and secondary molding methods such as vacuum molding, pressure molding, and vacuum pressure molding using sheets obtained by these molding methods. In addition, the resin composition of the present invention can be used alone to form a molded article such as a single-layer sheet, but since the resin composition of the present invention has excellent adhesion to thermoplastic resins, it is more effective to use the resin composition as a laminate containing one layer.

[0082] [Laminate] The laminate using the resin composition of the present invention is a laminate having two or more layers including a layer containing the resin composition of the present invention (hereinafter, sometimes referred to as "resin composition layer of the present invention"). Among these, a laminate having at least a first layer and a second layer, and having a resin composition layer of the present invention between the first layer and the second layer is particularly preferred. The shape of the laminate of the present invention is not limited, and may be any shape such as a planar shape such as a film, sheet, or plate, a pipe shape, a bag shape, or an indefinite shape. The material constituting the layer other than the resin composition layer of the present invention (hereinafter, sometimes referred to as "other layer") is not limited, and may be not only a resin layer but also a metal layer. The material of the resin layer constituting the laminate is not limited, and for example, those exemplified as other resins that can be used in the resin composition of the present invention can be mentioned, and a resin layer containing a thermoplastic resin is preferred. In addition, the resin layer constituting the laminate may contain an additive that can be used in the resin composition of the present invention.

[0083] Among these, laminates having the resin composition layer of the present invention as an adhesive layer and a polyurethane resin layer, a polycarbonate resin layer, a polyvinyl chloride resin layer, or a polyolefin resin layer as a resin layer containing a thermoplastic resin, particularly a polyvinyl chloride resin layer and / or a polyolefin resin layer described below, are suitable. In this case, the layer structure of the laminate is not limited, but a laminate in which the first layer is a polyvinyl chloride resin layer or a polyolefin resin layer, and the second layer is a polyvinyl chloride resin layer or a polyolefin resin layer is preferred. Among these, a laminate in which the first layer is a polyvinyl chloride resin layer and the second layer is a polyolefin resin layer is particularly preferred.

[0084] When the laminate of the present invention is used for building materials such as wallpaper and decorative sheets, it is preferable to use a polycarbonate resin layer or an aluminum layer, which is less susceptible to surface contamination and is also suitable in terms of hygiene and the environment, as the outer surface side, an adhesive layer made of the resin composition of the present invention as an intermediate layer, and a polyvinyl chloride resin layer, which has good flexibility and moldability, as the inner surface. In this case, a multilayer structure is formed by further providing an adhesive layer, a release layer, etc. on the polyvinyl chloride resin layer side, and the release layer can be peeled off before use.

[0085] <Polyvinyl chloride resin layer> The polyvinyl chloride resin layer constituting the laminate contains at least polyvinyl chloride resin. The polyvinyl chloride resin constituting the polyvinyl chloride resin layer is not limited, but may be a homopolymer or copolymer of vinyl chloride. The monomer copolymerizable with vinyl chloride is not limited, but may be, for example, ethylene, propylene, acrylonitrile, vinyl acetate, maleic acid or its ester, acrylic acid or its ester, methacrylic acid or its ester, or vinylidene chloride. It may also be a partially crosslinked resin. A polymer blend of polyvinyl chloride resin, for example, a polymer blend consisting of polyvinyl chloride resin and polyvinylidene chloride, may also be used. Of these, the polyvinyl chloride resin used in the polyvinyl chloride resin layer is preferably a homopolymer of vinyl chloride.

[0086] The average degree of polymerization of the polyvinyl chloride resin used in the polyvinyl chloride resin layer is not limited, but is usually 500 to 6000, and preferably 800 to 3000. The reduced viscosity (K value) of the polyvinyl chloride resin is not limited, but is usually 50 to 110, and preferably 60 to 90, as a value according to JIS K7367-2.

[0087] The method for producing the polyvinyl chloride resin is not limited, and it can be produced by, for example, a suspension polymerization method, a bulk polymerization method, or an emulsion polymerization method. It may also be a plastisol or an aqueous latex in which fine particles of polyvinyl chloride resin are dispersed in an organic medium.

[0088] The polyvinyl chloride resin used in the polyvinyl chloride resin layer preferably contains a plasticizer. The plasticizer used in the polyvinyl chloride resin is not particularly limited, and one or more of known plasticizers can be used.

[0089] The amount of the plasticizer to be used is not limited, but is usually 1 to 150 parts by mass, preferably 15 to 120 parts by mass, and more preferably 20 to 100 parts by mass, per 100 parts by mass of the polyvinyl chloride resin. When the amount of the plasticizer is equal to or more than the lower limit, the flexibility of the laminate of the present invention tends to be good. On the other hand, when the amount of the plasticizer is equal to or less than the upper limit, bleeding out of the plasticizer from the laminate of the present invention is suppressed, and the moldability is also good.

[0090] The polyvinyl chloride resin used in the polyvinyl chloride resin layer may contain a stabilizer. The stabilizer used in the polyvinyl chloride resin is not limited, but can be appropriately selected from known stabilizers for polyvinyl chloride resins, and examples thereof include tribasic lead sulfate, dibasic lead phthalate, lead silicate, lead orthosilicate-silica gel coprecipitate, dibasic lead stearate, cadmium-barium stabilizers, barium-zinc stabilizers, calcium-zinc stabilizers, tin stabilizers, and stabilizers mainly composed of inorganic salts of magnesium, aluminum, silicon, etc., such as hydrotalcite. These stabilizers may be used alone or in combination of two or more compounds.

[0091] The amount of the stabilizer to be used is not limited, but is usually 1 to 30 parts by mass, preferably 2 to 20 parts by mass, and more preferably 3 to 15 parts by mass, per 100 parts by mass of polyvinyl chloride resin. When the stabilizer is blended in the above range, the thermal stability and moldability tend to be good.

[0092] <Polyolefin resin layer> The polyolefin resin layer constituting the laminate contains at least a polyolefin resin. There are no limitations on the polyolefin resin that can be used in the polyolefin resin layer, and one type may be used alone, or two or more types may be used in combination. The polyolefin resin suitable for the polyolefin resin layer varies depending on the application and required properties of the laminate of the present invention, but when used as a building material, a polyethylene resin or a polypropylene resin is suitable. As the polyethylene resin, a copolymer of ethylene and an α-olefin having 3 to 8 carbon atoms is preferable, and as the polypropylene resin, a copolymer of propylene and ethylene or an α-olefin having 4 to 8 carbon atoms is preferable. In particular, since the resin composition of the present invention contains the above-mentioned component (B), and hence has particularly good adhesion to polypropylene-based resins, the polyolefin resin layer is preferably a polypropylene-based resin layer.

[0093] The melt flow rate (MFR) of the polyolefin resin used in the polyolefin resin layer is not limited, but is usually in the range of 0.1 to 100 g / 10 min, preferably 0.5 to 80 g / 10 min, and more preferably 1.0 to 60 g / 10 min. If the MFR is in the above range, the moldability of the laminate tends to be good. Here, the MFR is measured in accordance with JIS K7210 (1990), and is a value measured under conditions of 190°C and a load of 21.2 N when the polyolefin resin is a polyethylene resin or a poly-1-butene resin, and is a value measured under conditions of 230°C and a load of 21.2 N when the polyolefin resin is a polypropylene resin.

[0094] <Method of manufacturing laminate> The method for producing the laminate of the present invention is not limited, and various conventionally known methods can be adopted. In particular, since the resin composition of the present invention has good adhesiveness, it is possible to make a laminate having good adhesiveness by the following molding method without performing dry lamination using an organic solvent. For example, a method of making an inflation film, T-die film, sheet, pipe, etc. by a co-extrusion method in which individual molten resins melted in an extruder are supplied to a multi-layer die and laminated in the die, and a co-injection molding method in which individual molten resins are injected into the same mold with a time lag can be mentioned. In addition, an extrusion lamination molding method can be adopted in which a resin film constituting any one of the layers is molded in advance, and the other layers are melt-extruded thereto. Furthermore, it is also possible to mold the resin films constituting each layer in advance, and heat each of these layers to fuse them to make a laminate.

[0095] The laminate of the present invention can also be obtained by the above-mentioned molding method, and then stretched to form a stretched laminate. The stretched laminate can be heat-set or can be used as a product without heat-setting. If heat-setting is not performed, the stretched laminate can be used as a shrink film because it has a property of shrinking due to stress release by heating the stretched laminate thereafter. Furthermore, these can be used as a squeezed container or the like through secondary processing such as vacuum forming and pressure forming.

[0096] The thickness (total thickness) of the laminate of the present invention is not limited and can be set arbitrarily depending on the layer structure, application, shape of the final product, required physical properties, etc., but is usually 30 to 500 μm, preferably 40 to 400 μm, and more preferably 50 to 300 μm.

[0097] The thickness of the resin composition layer (adhesive layer) of the present invention in the laminate of the present invention is not limited and can be arbitrarily set depending on the layer structure, application, shape of the final product, required physical properties, etc., but is usually 1% or more, preferably 5% or more, and usually 20% or less, preferably 10% or less, of the total thickness. If the thickness of the resin composition layer of the present invention is the above lower limit or more, the adhesion becomes good, and if it is the above upper limit or less, the film strength tends to be improved. In the examples described later, the laminate and adhesive layer are thicker than the above upper limit in order to evaluate the adhesive strength.

[0098] <Application> Since the resin composition of the present invention has good adhesion to thermoplastic resins, the laminate obtained by using the resin composition of the present invention can be suitably used as building materials such as wallpaper and decorative sheets, and can also be widely applied to protective films for various molded products, antifouling films, packaging materials, etc. Among these, it can be particularly suitably used as wallpaper. When the laminate of the present invention is used as wallpaper, an adhesive layer, a base layer, an antifouling layer, a release layer, etc. may be further provided. In addition, physical treatment such as embossing may be performed, and in this case, good interlayer adhesion can be maintained. EXAMPLES

[0099] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples as long as it does not exceed the gist of the invention. The values ​​of various production conditions and evaluation results in the following examples are meant as preferred upper or lower limit values ​​in the embodiment of the present invention, and the preferred range may be a range defined by a combination of the above-mentioned upper or lower limit values ​​and the values ​​of the following examples or values ​​between the examples.

[0100] [Raw materials used] The raw materials used in the following examples and comparative examples are as follows.

[0101] <Component (A): Acrylic thermoplastic elastomer> (A-1) "Clarity (registered trademark) LA4285" manufactured by Kuraray Co., Ltd. Hard segment: methyl methacrylate polymer block (50% by mass) Soft segment: n-butyl acrylate polymer block (50% by mass) Weight average molecular weight (Mw): 58,000 Molecular weight distribution (Mw / Mn): 1.13 Glass transition temperature (Tg): 141℃, 29℃ MFR: 1.5g / 10min (190℃, 21.2N) Specific gravity: 1.110 Duro A hardness: 46

[0102] <Component (B): Propylene-based elastomer> (B-1) ExxonMobil "Vistamaxx (registered trademark) 3020FL" Density (ASTM D1505): 0.874g / cm 3 MFR:3.0g / 10min (230℃, 21.2N) Propylene unit content: 89% by mass (B-2) "Zelas (registered trademark) 7025" manufactured by Mitsubishi Chemical Corporation Density (ASTM D1505): 0.893g / cm 3 MFR: 1.8g / 10min (230℃, 21.2N)

[0103] <Component (C): Styrene-based thermoplastic elastomer> (C-1) Styrene-ethylene-butylene-styrene copolymer (SEBS) Asahi Kasei Corporation "Tuftec (registered trademark) H1517" Styrene unit content: 43% by mass MFR:3.0g / 10min (230℃, 21.2N) Density (ASTM D1505): 0.930g / cm 3 (C-2) Styrene-butadiene block copolymer and / or its hydrogenated product Asahi Kasei Corporation "SOE (registered trademark) S1605" MFR:5.0g / 10min (230℃, 21.2N) Density (ASTM D1505): 1.000g / cm 3 (C-3) Amine-modified styrene-ethylene-butylene-styrene copolymer (SEBS) Asahi Kasei Corporation "Tuftec (registered trademark) MP10" Styrene unit content: 30% by mass MFR:4.0g / 10min (230℃, 21.2N) Density (ASTM D1505): 0.910g / cm 3

[0104] <Component (D): Polyester elastomer> (D-1) Polyester-polyalkylene glycol block copolymer Hetroflex (registered trademark) H25DMG manufactured by Hetron Corporation Number average molecular weight of polytetramethylene glycol: 1,800 Polybutylene terephthalate unit content: 20% by mass Polytetramethylene glycol unit content: 80% by mass Melting point: 168℃ MFR: 18g / 10min (230℃, 21.2N) Specific gravity: 1.06 Duro A hardness: 82

[0105] <Component (E): Ethylene-vinyl acetate copolymer> (E-1) "Evaflex (registered trademark) EV150" manufactured by DuPont-Mitsui Polychemicals Co., Ltd. Vinyl acetate content: 33% by weight MFR:30.0g / 10min (190℃, 21.2N) Density: 0.960g / cm 3 Melting point: 61℃

[0106] [Examples 1 to 7 and Comparative Examples 1 and 2] Each raw material component was used in the mixing ratio shown in Table 1, and kneaded at 180 to 200 ° C. using a micro kneader to prepare pellets of a resin composition. The MFR, Duro D hardness, and flexural modulus of the prepared pellets of the resin composition were measured by the methods described later, and the results are shown in Table 1. Further, from the pellets of this resin composition, adhesive resin sheets of 1 mm thickness were molded using a press. A 1 mm thick polypropylene sheet and a 1 mm thick polyvinyl chloride sheet were overlapped with a width of 5 mm between them via the prepared adhesive resin sheet, and adhesion was performed under the following press conditions to prepare an evaluation sample. This evaluation sample was prepared by overlapping the edge portions of each sheet via the adhesive resin sheet so that the overlap width of the polypropylene sheet and the polyvinyl chloride sheet was 5 mm. <Press conditions> Temperature: 200℃ Preheat: No pressure, 4 minutes Pressure: 50kg / cm 2 , 3 minutes Cooling: 70kg / cm 2 , 3 minutes Spacer: 2mm

[0107] [Method for evaluating adhesive strength] The evaluation samples prepared in Examples 1 to 7 and Comparative Examples 1 and 2 were cut into 15 mm widths in a direction perpendicular to the overlapping portion of the 5 mm wide polypropylene sheet and the polyvinyl chloride sheet. The cut evaluation samples were held in a tensile tester by gripping the polypropylene sheet with one hand and the polyvinyl chloride sheet with the other hand, and pulled in the directions away from each other at 50 mm / min along the surfaces of each sheet to measure the shear peel strength. The measurements were carried out at room temperature (23°C), 60°C and 80°C, and the peel strengths in the shear peel test are shown in Table 1 as adhesive strengths.

[0108] [Method of measuring MFR] The resin composition pellets were measured at 190° C. and a load of 21.2 N in accordance with JIS K7210 (1999).

[0109] [Method of measuring Duro D hardness] Using the pellets of the resin composition, test pieces for measuring Duro D hardness (test pieces having a thickness of 4 mm, a width of 10 mm, and a length of 80 mm) were molded using an in-line screw type injection molding machine ("FE80S12ASE" manufactured by Nissei Plastic Industrial Co., Ltd.) at an injection pressure of 20-40 MPa, a cylinder temperature of 200°C, and a mold temperature of 40°C. The Duro D hardness (after 15 seconds) of these test pieces was measured in accordance with JIS K6253 using a measuring device ("P2 Autodurometer" manufactured by Kobunshi Keiki Co., Ltd.).

[0110] [Method for measuring flexural modulus] Using pellets of the resin composition, test pieces for measuring the flexural modulus (test pieces having a thickness of 4 mm, a width of 10 mm, and a length of 80 mm) were molded using an in-line screw type injection molding machine ("FE80S12ASE" manufactured by Nissei Plastic Industrial Co., Ltd.) at an injection pressure of 20-40 MPa, a cylinder temperature of 200°C, and a mold temperature of 40°C. The flexural modulus (unit: MPa) of these test pieces was measured at a span of 64 mm and a bending speed of 2 mm / min in accordance with JIS K7171.

[0111] [Table 1]

[0112] From Table 1, it can be seen that the resin composition of the present invention containing components (A), (B), and (C) has high adhesive strength with polyvinyl chloride resin and maintains high adhesive strength even under high temperature conditions. Since it has been measured that the resin composition of the present invention maintains high adhesive strength with vinyl chloride resin, it can be seen that it also maintains good adhesiveness and heat-resistant adhesiveness with polypropylene resin.

[0113] In contrast, Comparative Example 1, in which component (D-1), a polyester elastomer, was used instead of component (A), and component (E-1), an ethylene-vinyl acetate copolymer, was used instead of component (C), corresponds to the resin composition of Patent Document 2, but showed poor adhesive strength with polyvinyl chloride resin under high temperature conditions. Comparative Example 2, in which ethylene-vinyl acetate copolymer (E-1) was used instead of component (C), corresponds to the resin composition of Patent Document 1. However, this Comparative Example 2 also peeled off at the interface with the polypropylene sheet under high temperature conditions, and the adhesive strength to the polyvinyl chloride resin could not be confirmed.

Claims

1. A resin composition comprising the following components (A), (B) and (C): A resin composition, in which the content of component (A) is 20 to 65 mass%, the content of component (B) is 20 to 65 mass%, and the content of component (C) is 10 to 50 mass%, relative to the total amount of components (A), (B), and (C). Component (A): Acrylic thermoplastic elastomer which is an acrylic block copolymer Component (B): Propylene-based elastomer Component (C): Styrene-based thermoplastic elastomer

2. 2. The resin composition according to claim 1, wherein the acrylic thermoplastic elastomer of component (A) is a polymethyl methacrylate-polybutyl acrylate block copolymer.

3. A molded article obtained by molding the resin composition according to claim 1 or 2.

4. A laminate comprising a layer containing the resin composition according to claim 1 or 2 and another layer.

5. The laminate according to claim 4, comprising at least a first layer and a second layer as the other layers, and a layer containing the resin composition between the first layer and the second layer.

6. The laminate according to claim 4 or 5, wherein the another layer is a resin layer containing a thermoplastic resin.

7. The laminate according to claim 6 , wherein the resin layer containing a thermoplastic resin comprises a polyvinyl chloride resin layer.

8. The laminate according to claim 5 , wherein the first layer is a polyvinyl chloride resin layer or a polyolefin resin layer, and the second layer is a polyvinyl chloride resin layer or a polyolefin resin layer.

9. 9. The laminate according to claim 8, wherein the first layer is a polyvinyl chloride resin layer and the second layer is a polyolefin resin layer.

10. A building material comprising the laminate according to any one of claims 4 to 9 as a component.

Citation Information

Patent Citations

  • Polypropylene resin composition for thermoforming and polypropylene resin sheet

    JP2002249625A

  • Non-halogen flame-retardant resin composition

    JP2005314516A

  • Flame-retardant resin composition and molded product using the same

    JP2006199951A

  • Base material with resealing function and package using this base material

    JP2008200960A

  • Insulated electric cable excellent in weatherability

    JP2009054388A